Analysis of the Implementation of the Merdeka Curriculum in Developing Early Childhood Character at TK Negeri Pembina Dewi Kayangan in the 2024/2025 Academic Year - Sari, Titik Puspa; Hamdani, Muh.; Mahendra, Juandra Prisma (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to describe the implementation of the independent curriculum in developing student character and to identify the supporting and inhibiting factors of the independent curriculum in developing student character at TKN Pembina Dewi Kayangan in the 2024/2025 academic year. This research is a descriptive qualitative study. Data collection techniques include observation, interviews, and documentation. The data obtained are analyzed descriptively through data reduction, data presentation, and conclusion drawing. Data validity testing or data validity checking uses triangulation, member checking, and peer review. The results of the study indicate that 1) the implementation of the independent curriculum in developing the character of students at TKN Pembina Dewi Kayangan in the five dimensions of the Pancasila student profile, namely being faithful, reverent to God Almighty, and having noble character, being globally diverse, thinking critically, being independent and creative, instills good character such as saying prayers before and after studying, being polite, respecting differences among peers, being willing to cooperate in small groups, helping friends in need, performing simple tasks without assistance, asking questions when something is not understood, and being able to produce simple works through habitual activities. 2) Supporting factors of the independent curriculum in developing the character of students at TKN Pembina Dewi Kayangan a) The availability of facilities that serve as supporting infrastructure for habit formation, such as a prayer room as a place for children to practice worship, play equipment, trash bins, cleaning equipment, and a playground. b) Support from the school principal and parents in student-centered activities. Meanwhile, the inhibiting factors are: a) The presence of some students who are less conducive during the activities. b) The limitations of teachers in supervising students in developing habits only within the school environment. c) The limitations of reference books and internet access, which are not yet facilitated. This becomes an obstacle because the internet is an important source of information and learning materials